IMPLEMENTASI PMM DALAM PENILAIAN KINERJA GURU SEKOLAH DASAR (STUDI MULTI KASUS PADA TIGA SEKOLAH DASAR DI KABUPATEN WAJO) - Yulianti, Andi; Arismunandar; Muhammad Ardiansyah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to describe the utilization of the Merdeka Mengajar Platform (PMM) in teacher performance evaluations and identify its supporting and inhibiting factors in three elementary schools in Wajo Regency: UPTD SD Negeri 1 Padduppa (Accreditation A), UPTD SD Negeri 258 Teddaopu (Accreditation B), and UPTD SD Negeri 405 InalipuE (Accreditation C). A qualitative method with a multiple case study design was employed. Research subjects included principals and teachers from each school.The findings revealed active use of PMM in teacher performance evaluations. UPTD SD Negeri 1 Padduppa implemented PMM smoothly, while UPTD SD Negeri 258 Teddaopu encountered technical challenges and policy flexibility issues. UPTD SD Negeri 405 InalipuE faced greater challenges, such as limited internet access and high workloads. Supporting factors included available technology, stable internet connections, teacher collaboration, and principal support. Inhibiting factors included technical issues, limited internet access, and lack of training. This study is expected to provide insights into improving PMM implementation to support educational quality in remote areas.